2014
DOI: 10.4315/0362-028x.jfp-13-357
|View full text |Cite
|
Sign up to set email alerts
|

Internalization and Fate of Escherichia coli O157:H7 in Leafy Green Phyllosphere Tissue Using Various Spray Conditions

Abstract: In the past decade, leafy greens have been implicated in several outbreaks of foodborne illness, and research has focused on contamination during preharvest operations. Concerns have been raised that internalization of pathogens into the edible tissue occurs where postharvest chemical interventions would be ineffective. This study was initiated to measure the degree and fate of Escherichia coli O157:H7 internalized in the phyllosphere tissue of leafy greens when spray conditions, inoculum level, and type of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…With the exception of the 'Capture' cultivar, the percentage of plants with internalized cells in their phyllosphere tissue at 24 h decreased from that which had been observed at 1 h and those decreases ranged from 7% to 43% (Table 1). In contrast to a previous study, the prevalence of internalized E. coli O157:H7 in spinach had dropped more dramatically, initially being 100% and dropping to 7.5% after 24 h. 28 In fact, due to the limited number of samples analyzed at 24 h in this experimental trial, the only cultivar that exhibited a significant drop in prevalence of internalized Salmonella within 24 h after exposure was 'Fast Vantage'. In that case, the probability that a sample positive for internalized Salmonella would be identified at 24 h was 10.5 times less likely than at 1 h [95% confidence interval (CI) from 0.7 to 153, P = 0.0468].…”
Section: Salmonella Internalization Into Small Cabbage Plantscontrasting
confidence: 93%
“…With the exception of the 'Capture' cultivar, the percentage of plants with internalized cells in their phyllosphere tissue at 24 h decreased from that which had been observed at 1 h and those decreases ranged from 7% to 43% (Table 1). In contrast to a previous study, the prevalence of internalized E. coli O157:H7 in spinach had dropped more dramatically, initially being 100% and dropping to 7.5% after 24 h. 28 In fact, due to the limited number of samples analyzed at 24 h in this experimental trial, the only cultivar that exhibited a significant drop in prevalence of internalized Salmonella within 24 h after exposure was 'Fast Vantage'. In that case, the probability that a sample positive for internalized Salmonella would be identified at 24 h was 10.5 times less likely than at 1 h [95% confidence interval (CI) from 0.7 to 153, P = 0.0468].…”
Section: Salmonella Internalization Into Small Cabbage Plantscontrasting
confidence: 93%
“…; Erickson et al . ). Salmonella and Shiga toxigenic E. coli have been the main focus (Brandl ; Brandl et al .…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of artificially inoculated human pathogens has been investigated on many different types of leafy vegetables, such as lettuce, spinach and rocket (Cooley et al 2006;Alam et al 2014;Erickson et al 2014). Salmonella and Shiga toxigenic E. coli have been the main focus (Brandl 2004;Brandl et al 2013;Moyne et al 2013; and various routes of transmission have been studied (Brandl 2006;Mandrell 2009;Farrar and Guzewich 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Van der Linden and colleagues (2013) demonstrated that overhead sprinkle irrigation was associated with increased enteric pathogen contamination of butterhead lettuce. Repeated spray irrigation with a low dose (approximately 3.5 log CFU ml −1 ) of E. coli O157:H7 resulted in internalization of the pathogen in spinach and parsley leaves, but not in lettuce leaves (Erickson et al, 2014). The pathogen persisted for 2 days post-exposure, suggesting that irrigation immediately prior to harvest presents an increased microbiological risk.…”
Section: Irrigation Watermentioning
confidence: 98%